Quantitative Imaging of Ozone Vapor Using Photofragmentation Laser-Induced Fluorescence (LIF). Issue 7 (July 2017) - Larsson, Kajsa; Hot, Dina; Ehn, Andreas; Lantz, Andreas; Weng, Wubin; Aldén, Marcus; Bood, Joakim
In the present work, the spectral properties of gaseous ozone (O3 ) have been investigated aiming to perform quantitative concentration imaging of ozone by using a single laser pulse at 248 nm from a KrF excimer laser. The O3 molecule is first photodissociated by the laser pulse into two fragments, O and O2 . Then the same laser pulse electronically excites the O2 fragment, which is vibrationally hot, whereupon fluorescence is emitted. The fluorescence intensity is found to be proportional to the concentration of ozone. Both emission and absorption characteristics have been investigated, as well as how the laser fluence affects the fluorescence signal. Quantitative ozone imaging data have been achieved based on calibration measurements in known mixtures of O3 . In addition, a simultaneous study of the emission intensity captured by an intensified charge-coupled device (ICCD) camera and a spectrograph has been performed. The results show that any signal contribution not stemming from ozone is negligible compared to the strong fluorescence induced by the O2 fragment, thus proving interference-free ozone imaging. The single-shot detection limit has been estimated to ∼400 ppm. The authors believe that the presented technique offers a valuable tool applicable in various research fields, such as plasma sterilization, water and soil remediation, and plasma-assisted combustion.